The Singapore Convention on Mediation and the New York Convention on Arbitration: Comparing enforcement mechanisms and drawing lessons for Asia - CHUA, Eunice (Institutional Knowledge at Singapore Management University, 2020)
This article considers the enforcement mechanism for international mediated settlement agreements proposed by the Singapore Convention on Mediation and critically examines this mode of enforcement as against enforcement as an arbitral award in Asia, including through a hybrid process like Arb-Med-Arb. Similarities and differences between the New York Convention and the Singapore Convention on Mediation will be discussed and used to consider how Asian jurisdictions may respond to the Singapore Convention on Mediation and what lessons may be learnt from the arbitration context.